Mechanism of miR-218-5p in autophagy, apoptosis and oxidative stress in rheumatoid arthritis synovial fibroblasts is mediated by KLF9 and JAK/STAT3 pathways. (8th February 2021) - Chen, Ming; Li, Minghui; Zhang, Na; Sun, Wenwen; Wang, Hui; Wei, Wei
Abstract : This study was aimed to investigate the effects of miR-218-5p on the proliferation, apoptosis, autophagy, and oxidative stress of rheumatoid arthritis synovial fibroblasts (RASFs), and the related mechanisms. Quantitative reverse transcription–PCR showed that the expression of miR-218-5p in rheumatoid arthritis synovial tissue was significantly higher than that in healthy synovial tissue. Compared with healthy synovial fibroblasts, miR-218-5p expression was obviously upregulated in RASFs, while KLF9 protein expression was markedly downregulated. Mechanistically, miR-218-5p could directly bind to the 3′ untranslated region of KLF9 to inhibit the expression of KLF9. Additionally, transfection of miR-218-5p small interfering RNA (siRNA) inhibited the proliferation but promoted apoptosis and autophagy of RASFs. Simultaneously, miR-218-5p silencing reduced reactive oxygen species and malondialdehyde levels and increased superoxide dismutase and glutathione peroxidase activity to improve oxidative stress in RASFs. More importantly, the introduction of KLF9 siRNA reversed the effects of miR-218-5p siRNA transfection on RASF proliferation, apoptosis, autophagy, and oxidative stress. What is more, silencing miR-218-5p inhibited the activation of JAK2/STAT3 signaling pathway by targeting KLF9. Collectively, knockdown of miR-218-5p could regulate the proliferation, apoptosis, autophagy and oxidative stress of RASFs by increasing the expression of KLF9 and inhibiting the activation of the JAK2/STAT3 signaling pathway, which may provide a potential target for the mechanism research of RA.